Analisis Efektifitas Penerimaan Retribusi Parkir Dalam Meningkatkan Pendapatan Asli Daerah - Runtu, Muhamad Rasdy Gery; Razak, Nirwan; Tarang, Bustan; Umar, Fahruddin Andi; Abdullah, A. Ruslan (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
Original Regional Income (PAD) is all regional revenue originating from original regional economic sources. Therefore, efforts to increase revenue from Regional Original Income (PAD) need to receive serious attention from regional governments, either through intensification or extensification with the aim that regions do not depend too much/rely on expectations from top level government but must be able to be independent in accordance with the ideals of real autonomy. and responsible. Exploring potential funds includes, among other things, collecting regional taxes and regional levies. This research uses quantitative descriptive research with data collection techniques through observation, interviews and documentation which aims to determine the growth of parking levy receipts, the effectiveness of parking levy receipts and determine the contribution of parking levies to local revenue in Parepare City from 2019 to 2022. The research results show that the growth in parking levy revenue in Parepare City in 2019-2022 was 8.14%, the effectiveness of parking levy revenue in Parepare City for the 2018-2021 period averaged 74.27%, this is considered less effective. Contribution to parking levy revenue in Parepare City from 2018-2021 is considered to be under-contributing with an average value of 1.06% of Parepare City's Original Regional Revenue.